Επιγραφές και σπαράγματα από την Έδεσσα, την Άρνισσα και την Αλμωπία - Χρυσοστόμου, Αναστασία; Καλαϊτζή, Μύρινα; Πασχίδης, Πασχάλης (Tekmeria, 2015)
Seventeen (17) inscribed monuments are presented in this article. Most of them (nos. 1-13) are findings from the area of the Citadel and of the Lower City of ancient Edessa, Macedonia, two of them come from the neighbouring site of modern Arnissa and, lastly, another two come from the region of ancient Almopia, Macedonia. Dating to the Roman Imperial and Early Christian periods, most of them belong to the class of funerary monuments. Humble in their majority as they may be, they are hereby grouped together as they yield new material as to the onomastikon, funerary poetry, as well as to the sculptural production and funerary iconographic repertory of ancient Edessa and adjacent areas.